Modified Peritoneal Flap Hernioplasty Versus Retromuscular Technique for Incisional Hernia Repair: a Retrospective Cohort Study. (December 2020) - Petersson, P.; Montgomery, A.; Petersson, U.
Background and Aims: We present an open retromuscular mesh technique for incisional hernia repair, the modified peritoneal flap hernioplasty, where the fascia is sutured to the mesh and the hernia sac utilized for anterior mesh coverage. The aim was to describe the modified peritoneal flap hernioplasty technique and to compare it to a retromuscular repair, without component separation, regarding short-term complications, patient satisfaction, abdominal wall complaints, and recurrent incisional hernia. Materials and Methods: Consecutive patients operated electively with modified peritoneal flap hernioplasty technique (December 2012–December 2015) or retromuscular technique (Jan 2011–Oct 2014) were included in a retrospective single-center cohort study. Outcomes were evaluated from the Swedish Ventral Hernia Registry, by chart review, physical examination, and an abdominal wall complaints questionnaire. Results: The modified peritoneal flap hernioplasty group ( n  = 78) had larger hernias (mean width 10.4 vs 8.5 cm, p  = 0.005), more advanced Centers for Disease Control classification ( p  = 0.009), and more simultaneous gastrointestinal-tract surgery (23.1% vs 11.5%, p  = 0.041) than the retromuscular group ( n  = 96). No difference in short-term complications was seen. Incisional hernia recurrence was lower in the modified peritoneal flap hernioplasty group (1.4% vs 10.3%, p  = 0.023), and patients were more satisfied (93.8% vs 81.7%, p  = 0.032). Follow-up time was shorter in the modified peritoneal flap hernioplasty group (614 vs 1171 days, p  < 0.001). Conclusion: This retrospective study showed similar rates of short-term complications, despite more complex hernias in the modified peritoneal flap hernioplasty group. Furthermore, a lower incisional hernia recurrence rate for the modified peritoneal flap hernioplasty technique compared with the retromuscular technique used in our department was found. If this holds true with equally long follow-up remains to be proven.